A proposed novel approach for torsional strength prediction of RC beams. (September 2019) - Ilkhani, M.H.; Naderpour, H.; Kheyroddin, A.
Abstract: The inadequate torsional moment capacity of a member can lead to the emergence of significant stress and even irreparable damage to the structure. In the present study, a new approach for estimating the torsional capacity and an equation for predicting the maximum torsional strength of rectangular RC beams has been proposed. The main purpose of this study was therefore to obtain an accurate equation for the estimation of this parameter. To this end, the reliable and homogeneous experimental data collected from the literature were used to train an artificial neural network. The impact of variations in different parameters on the network output was then investigated. Ultimately, an equation for estimating the torsional capacity of rectangular RC beams was formulated. The obtained equation needs the beam dimensions, the compressive strength of the concrete, and the specifications of the longitudinal and transverse reinforcement as input, and gives the ultimate torsional strength of the rectangular RC beam as output. Finally, the proposed equation was compared with the equations provided in the prominent building codes. Highlights: The main purpose of this study was to obtain an accurate equation for the estimation of this parameter. The impact of variations in different parameters on the network output was investigated. An equation for estimating the torsional capacity of rectangular RC beams was formulated. The proposed equation was compared with the equations provided in the prominent building codes.